Answer:
y= -3x +2
Explanation:
Slope-intercept form:
y= mx +c, where m is the gradient and c is the y-intercept.
![\boxed{slope = (y1 - y2)/(x1 - x2) }](https://img.qammunity.org/2021/formulas/mathematics/high-school/uzkys24gps6hs38r36ztlgl72pwrbbprih.png)
* (x1, y1) is the first coordinate and (x2,y2) is the second coordinate.
Let's find the gradient of the line.
![m = (5 - ( - 1))/( - 1 - 1) \\ m = (5 + 1)/( - 2) \\ m = (6)/( - 2) \\ m = - 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/juxmxkj6x093l4rnrdukqlw0xzma37wxji.png)
Substitute m= -3 into the equation:
y= -3x +c
Since y-intercept is at (0, 2), c= 2.
Substitute c= 2 into the equation:
y= -3x +2
The closest option will be the first option. However, since the x-axis is labelled as x not z, the equation should be y= -3x +2 not y= -3z +2.